Children’s education and parental old-age health: evidence from a population-based, nationally representative study in India - Thoma, Berenike; Sudharsanan, Nikkil; Karlsson, Omar; Joe, William; Subramanian, S. V.; De Neve, Jan-Walter (Population studies, 2021)
Previous research has documented intergenerational transmission of human capital from children to parents. Less is known, however, about heterogeneity in this ‘upward transmission’ in low-resource settings. We examine whether co-resident adult children’s education is associated with improved health among older parents in India, using nationally representative data from the 2014 Indian National Sample Survey. Parents of children with tertiary education had a lower probability of reporting poor health than parents of children with less than primary education. The benefits of children’s education persisted after controlling for economic factors, suggesting that non-pecuniary pathways—such as health knowledge or skills—may play an important role. The association was more pronounced among economically dependent parents and those living in the North and West regions. Taken together, our results point to a strong positive association between children’s education and parental health, the role of non-pecuniary pathways, and the importance of subnational heterogeneity in India.